Comparison of Fungal Communities at Peak Total Microbial Colony Count during Alcohol and Acetic Acid Fermentation in Shanxi Aged Vinegar under Different Production Modes and Seasons - Xin ZHAO; Yujing ZHANG; Xufeng CHEN; Nü XU (Shipin gongye ke-ji)
To investigate the diversity of fungal community structures in Shanxi aged vinegar under different production modes and seasons, high-throughput sequencing technology was employed in this study to detect the fungal diversity in samples collected during the peak periods of microbial colony counts in both alcohol fermentation and acetic acid fermentation processes. These samples represented traditional manual production and modern mechanical production modes across different seasons. The results showed that 41 and 45 fungal genera were detected in alcohol fermentation mash (Jiulao) samples at peak total microbial colony count under traditional manual and modern mechanical production modes. Based on the average relative abundance of fungal genera across four seasons, the dominant fungal genera under traditional manual production mode were Saccharomyces (21.36%), Aspergillus (11.76%), Thermoascus (5.16%), and Kazachstania (2.89%). In contrast, the dominant fungal genera under modern mechanical mode were Aspergillus (29.88%), Candida (25.43%), Saccharomyces (6.68%), Kazachstania (3.81%), and Mortierella (2.26%). During acetic acid fermentation, fermentation grains (Cupei) samples from traditional manual and modern mechanical production modes at peak total microbial colony count were found to contain 55 and 70 fungal genera, respectively. The dominant fungal genera under traditional manual mode were Kazachstania (2.41%), Aspergillus (2.58%), Filobasidium (3.75%), Saccharomyces (7.59%), Alternaria (14.98%) and Cladosporium (18.09%). In contrast, the dominant fungal genera under modern mechanical mode were Candida (2.65%), Aspergillus (4.33%), Cladosporium (9.69%) and Alternaria (15.80%). The fungal community structures of Jiulao and Cupei showed significant differences across different seasons. Moreover, the diversity and community structure of fungi exhibited distinct differences under different production modes.